Misuse of Dakwah as Religious Tyranny in the Film Bidaah: A Critical Discourse Analysis - Munib, Abd; Humaidy, Mohammad Ali Al; Choliq, Abdul; Jauhari, Minan (LifeSciFi, 2025)
This article explores the tyranny of dakwah in the Malaysian film Bidaah. Dakwah, which should guide audiences toward Sharia, is instead portrayed as a tool of oppression. The study employs critical discourse analysis based on Norman Fairclough’s framework, examining textual elements, discourse practices, and the broader social context that shapes them. The findings highlight three key points. First, dakwah shifts from a spiritual mission to an instrument of social control, evident in how followers are forced to accept teachings uncritically, thus legitimizing violence in the name of religion. Second, dakwah is depicted as a dominant discourse across micro, meso, and macro dimensions. The micro dimension is seen in the rhetorical strategies used by Walid Muhammad to assert absolutism. The meso dimension involves dakwah being structured, closed, and ritualistic, transforming it from a dialogue to domination. At the macro level, the dakwah discourse reinforces unjust and exploitative social structures. Third, the film introduces a counter-discourse that challenges the tyranny of dakwah. Baiduri becomes the central figure who resists injustice and constructs an alternative narrative that confronts Walid’s authority. This study contributes to the scholarly understanding of religious discourse in film, offering a foundation for further research into similar representations in cinema.